A Lyotropic Chiral Smectic C Liquid Crystal with Polar Electrooptic Switching1. Issue 34 (6th August 2013) - Bruckner, Johanna R.; Porada, Jan H.; Dietrich, Clarissa F.; Dierking, Ingo; Giesselmann, Frank
<x xml:space="preserve">Abstract</x> A lyotropic analogue of the ferroelectric smectic C* phase has been found. The lyotropic smectic C* phase shows macroscopic chirality effects, such as a helical ground state and polarity‐dependent electrooptic switching, thus indicating the presence of a spontaneous electric polarization. The helicity implies communication of the chiral director twist across the achiral solvent layers separating adjacent layers of the chiral mesogens.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>